The Influence of Consumer Ethnocentrism on Intention Toward Domestic Electric Vehicle Selection - Wang, Zi-Xu; Wong, Philip Pong Weng*; Wang, Lei (Istanbul University-IUC Press, 2022)
Previous studies mostly investigated the individuals’ self-interested factors or functional attributes and intention toward purchasing electric vehicles based on the theory of planned behavior. Nevertheless, those studies neglected the irrational or impulsive factor which is consumer ethnocentrism influence on individuals’ decision-making processes. The current study aims to examine the relationship between consumer ethnocentrism, attitude, subjective norm, perceived behavioral control, and intention toward purchasing electric vehicles. A quantitative approach was applied using a survey technique involving 288 respondents. The proposed hypotheses were empirically tested with Statistical Package for Social Science and Analysis of Moment Structures (AMOS). The results showed that consumer ethnocentrism positively influenced attitude, subjective norm, perceived behavioral control, and intention. Attitude, subjective norm, and perceived behavioral control positively influenced intention. Meanwhile, attitude had a mediating role between subjective norm and intention, and subjective norm had a mediating role between consumer ethnocentrism and intention. This study extends the existing knowledge on how consumer ethnocentrism influences consumer intention to purchase electric vehicles in the marketing literature.